Economic empowerment of unbanked women through financial inclusion in Indonesia - Yenti Afrida; Irwan Abdullah; Zaenuddin Hudi Prasojo; Muthia Ulfah; Putri Ananda Saka; Jumni Nelli (Cogent Business & Management, 2024)
This study aims to elucidate the economic empowerment of unbanked women within the National Pension Savings Bank (BTPN) Sharia, focusing on the role of financial inclusion. It investigates how enhanced access to financing impacts the income and savings of the womenfolk operating home-based businesses in West Sumatra, Indonesia, using a qualitative methodology to delve into the empowerment pattern of unbanked women at BTPN Sharia. Data collection consisted of in-depth interviews and questionnaires, sourced from various stakeholders, such as customers, community officers, and BTPN Sharia leaders, followed by a thorough qualitative and descriptive analysis. The findings showed that the economic empowerment of unbanked women, driven by financial inclusion, is achieved through an initial membership training program consisting of financial literacy, management, and savings. This program also offers convenient access to financing and subsequent assistance, all conducted in a participatory manner referred to as `baropok', where women gather in a circle, facing the community officer. The financial inclusion-based empowerment model, emphasizing easy access to financing, has a positive impact on the income and savings of women engaged in home industry businesses in West Sumatra. These findings hold significant implications for the academic discourse on the economic empowerment of unbanked women within the framework of financial inclusion in Islamic Commercial banks.Gender inequality in the financial industry must be reduced by increasing women's financial inclusion. The primary objective of the financial inclusion policy is to narrow the gender gap in financial access to financial institutions. The economic empowerment of unbanked women is of significant importance as they serve as financial managers within households and play a crucial role in managing family expenses. BTPN Sharia empowerment of unbanked women based on financial inclusion had a positive impact on increasing the savings of females.
Keywords: 650; Financial inclusion; economic empowerment; unbanked women